So Much Truth, so Much Being: Poetic Provocations to Philosophical Musings - Elza, Daniela Bouneva; Manery, Robert; Cohen, Avraham (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
This bricolage of verses and prose, addresses the themes of poetics in and of philosophizing, and brings poetic provocations to philosophical musings. Authors muse on what it is to philosophize in the mood and mode of poetics, and why that matters for Education. Preliminary incursions are made into the issues of entrenched dualism between intellect (mind) and senses (heart), and ensuing privileging of the former over the latter. A collegially written introduction sets the general framework.